The Effect Of Audio Visual Media On The Learning Outcomes Of Pancasila Education Of Grade IV - Simarmata, Elisabeth; Siahaan, Theresia Monika; Simanjuntak, Bernard (CV Putra Publisher, 2025)
This study aims to determine whether audio-visual learning media influences the learning outcomes of fourth-grade students in Pancasila Education at State Elementary School 091254 Batu Onom. This research is quantitative. The sample used in this study was a population of 24 fourth-grade students. Data collection techniques included a pretest (before treatment) and a posttest (after treatment), as well as documentation. Data analysis techniques used the N-Gain test and hypothesis testing. The researchers then conducted an N-Gain test, with an average N-Gain score of 0.63, where 0.3 ≤ g ≤ 0.7 indicates that the learning outcomes were categorized as quite effective. The researchers then conducted a hypothesis test, which yielded a calculated tcount of 20.528 and a ttable value of 1.714 at a 5% significance level. Because tcount > ttable, H0 was rejected and Ha was accepted, indicating a significant influence of the use of Audio-Visual Media on the learning outcomes of fourth-grade students in SD Negeri 091254 Batu Onom.